2001
DOI: 10.1021/ic010298+
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear Hydroxamate Five-Coordinate Nickel(II) Complexes:  Structural and Spectroscopic Characterization

Abstract: Novel nickel complexes containing {O,O}-chelating hydroxamate ligands were prepared by attack of the hydroxamic acid by the hydroxo ligand, and the crystal structure shows the nickel atom in a five-coordinate environment that has structural features similar to those of inhibited urease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 22 publications
(35 reference statements)
0
19
0
Order By: Relevance
“…As described in Scheme 1 c, the acid±base reaction provided higher yields (82±93 %) and could be applied to the synthesis of the phosphinate-bridged complexes [{Ni( [12] E(P) transitions, respectively. [12] Both l max values and molar absorptivities are consistent with a five-coordinate environment around the nickel(ii) ion, [13] and provide evidence that the molecule maintains its integrity in solution.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…As described in Scheme 1 c, the acid±base reaction provided higher yields (82±93 %) and could be applied to the synthesis of the phosphinate-bridged complexes [{Ni( [12] E(P) transitions, respectively. [12] Both l max values and molar absorptivities are consistent with a five-coordinate environment around the nickel(ii) ion, [13] and provide evidence that the molecule maintains its integrity in solution.…”
Section: Resultsmentioning
confidence: 72%
“…The IR spectra of complexes 1±12 show characteristic absorptions for the [12]aneN 3 ligands [13] : 3291±3258 cm À1 n(NÀH),~1660 cm À1 n(C=N), and two strong bands as a result of the PF 6 À ion at 840 and 560 cm…”
Section: Resultsmentioning
confidence: 99%
“…This synthetic method has previously been used for the preparation of pentacoordinate nickel(ii) complexes containing N,S-donor, [10] oxamidate, [11] hydroxamate, [12] and pyridonate ligands, [13] as well as phosphate esters and phosphinate derivatives. [14] Complexes 1-4 are air-stable both in the solid state and in solution.…”
Section: Synthesis and Characterization Of Monomeric Pyridinecarboxylmentioning
confidence: 99%
“…They have been characterized by partial elemental analyses, FAB + mass spectrometry and spectroscopic (IR, UV/Vis, and 1 H NMR) methods. The IR spectra of complexes 1-4 show characteristic absorptions for the mcN 3 ligands: [12,14] 3287-3121 cm -1 for ν(N-H), ca. 1660 cm -1 for ν(C=N), and two strong bands as a result of the PF 6 -ion at 840 and 560 cm -1 .…”
Section: Synthesis and Characterization Of Monomeric Pyridinecarboxylmentioning
confidence: 99%
“…Metal complexes of hydroxamic acids have also attracted considerable attention because of their tautomerisation [14] exhibiting hydroxamic or hydroximic acid forms. The theoretical and experimental studies have suggested that the hydroxamic form is prevalent in free acids [15] or metal hydroxamates [16]. Fewer studies have described vanadium (IV) and (V) hydroxamate complexes as compared to many other transition metal hydroxamates [17][18][19][20][21] whereas vanadyl sulphate, ammonium vanadate and vanadyl acetylacetonate have been exploited as precursors [22].…”
Section: Introductionmentioning
confidence: 99%